2010
DOI: 10.1083/jcb.201006025
|View full text |Cite
|
Sign up to set email alerts
|

MyoD regulates apoptosis of myoblasts through microRNA-mediated down-regulation of Pax3

Abstract: Suppression of the myogenic transcription factor MyoD is required for maintenance of muscle stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(186 citation statements)
references
References 68 publications
4
178
0
Order By: Relevance
“…The behavior of adult muscle stem cells-particularly their proliferation, differentiation, and apoptosis-is regulated by Pax3 and the closely related Pax7. The protein levels of Pax3/7 were recently demonstrated to be tightly regulated by miRNAs, including miR-27b and miR-206 (12,40,41). Thus, embryonic myoblasts and adult muscle stem cells require mechanisms to tightly regulate Pax3/ Pax7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of adult muscle stem cells-particularly their proliferation, differentiation, and apoptosis-is regulated by Pax3 and the closely related Pax7. The protein levels of Pax3/7 were recently demonstrated to be tightly regulated by miRNAs, including miR-27b and miR-206 (12,40,41). Thus, embryonic myoblasts and adult muscle stem cells require mechanisms to tightly regulate Pax3/ Pax7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also reported miRNA mediated regulation of PAX3. 36 A subset of ARMS is characterized by PAX7-FOXO1 translocation; a recent study has shown that both miR-1 and -206 can potentially regulate PAX7 in skeletal muscle satellite cells. 37 Based on these evidences, we propose that loss of 3 0 UTR of PAX3/PAX7 and /or the downregulation of miR-1 and -206 are oncogenic events in rhabdomyosarcomagenesis ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Myoblasts are characterized by coexpression of Pax3 and Pax7, transcription factors involved in the specification and maintenance of skeletal muscle progenitors. [42][43][44] In our hands, a strong downregulation of Pax3 and Pax7 was observed between D7 and D14, while MyoG expression remains stable and MyoD was upregulated. These data are consistent with previous published studies reporting that Pax7 is rapidly downregulated in cells that commit to terminal differentiation.…”
Section: Cells Cultured In Three Different Conditions (On Sis In Petrimentioning
confidence: 64%